Indirect influence of soil enzymes and their stoichiometry on soil organic carbon response to warming and nitrogen deposition in the Tibetan Plateau alpine meadow - Xuemei, Xiang; Kejia, De; Weishan, Lin; Tingxu, Feng; Fei, Li; Xijie, Wei (Frontiers in Microbiology, 2024)
Despite extensive research on the impact of warming and nitrogen deposition on soil organic carbon components, the response mechanisms of microbial community composition and enzyme activity to soil organic carbon remain poorly understood. This study investigated the effects of warming and nitrogen deposition on soil organic carbon components in the Tibetan Plateau alpine meadow and elucidated the regulatory mechanisms of microbial characteristics, including soil microbial community, enzyme activity, and stoichiometry, on organic carbon components. Results indicated that both warming and nitrogen deposition significantly increased soil organic carbon, readily oxidizable carbon, dissolved organic carbon, and microbial biomass carbon. The interaction between warming and nitrogen deposition influenced soil carbon components, with soil organic carbon, readily oxidizable carbon, and dissolved organic carbon reaching maximum values in the W0N32 treatment, while microbial biomass carbon peaked in the W3N32 treatment. Warming and nitrogen deposition also significantly increased soil Cellobiohydrolase, β-1,4-N-acetylglucosaminidase, leucine aminopeptidase, and alkaline phosphatase. Warming decreased the soil enzyme C: N ratio and C:P ratio but increased the soil enzyme N:P ratio, while nitrogen deposition had the opposite effect. The bacterial Chao1 index and Shannon index increased significantly under warming conditions, particularly in the N32 treatment, whereas there were no significant changes in the fungal Chao1 index and Shannon index with warming and nitrogen addition. Structural equation modeling revealed that soil organic carbon components were directly influenced by the negative impact of warming and the positive impact of nitrogen deposition. Furthermore, warming and nitrogen deposition altered soil bacterial community composition, specifically Gemmatimonadota and Nitrospirota, resulting in a positive impact on soil enzyme activity, particularly soil alkaline phosphatase and β-xylosidase, and enzyme stoichiometry, including N:P and C:P ratios. In summary, changes in soil organic carbon components under warming and nitrogen deposition in the alpine meadows of the Tibetan Plateau primarily depend on the composition of soil bacterial communities, soil enzyme activity, and stoichiometric characteristics.